2015
DOI: 10.1016/j.infbeh.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Nine-month-old infants are sensitive to the temporal alignment of prosodic and gesture prominences

Abstract: This study investigated the sensitivity of 9-month-old infants to the alignment between prosodic and gesture prominences in pointing-speech combinations. Results revealed that the perception of prominence is multimodal and that infants are aware of the timing of gesture-speech combinations well before they can produce them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
11
0
2
Order By: Relevance
“…However, whether they can process and learn from physically less salient but nonetheless informative signals such as the EB movement used in this study remains unknown. Indeed, it is important to note that even if the EB movement in this study was not informative per se, EB movements usually provide useful information for the recognition of certain components of visual speech prosody that infants learn to process audiovisually during infancy (e.g., Esteve‐Gibert et al., ). Further studies should examine this issue.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, whether they can process and learn from physically less salient but nonetheless informative signals such as the EB movement used in this study remains unknown. Indeed, it is important to note that even if the EB movement in this study was not informative per se, EB movements usually provide useful information for the recognition of certain components of visual speech prosody that infants learn to process audiovisually during infancy (e.g., Esteve‐Gibert et al., ). Further studies should examine this issue.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, the eye region also affords social (e.g., eye‐gaze direction) and emotional (e.g., eyebrow movements) information (Csibra, ) that are essential to the understanding of the whole situation of communication. The eyebrow movements also provide a wide range of information, notably essential for the recognition of certain emotions (Ekman, ) or of certain component of visual speech prosody (Esteve‐Gibert, Prieto, & Pons, ). Accordingly, when asked to identify the emotion of a face talking in their native language, adults prefer directing their attention at the eyes region of the speaker (Buchan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…This is true in adults ( Hadar et al, 1983 ; De Ruiter, 1998 ; Leonard and Cummins, 2011 ; Esteve-Gibert and Prieto, 2013 ; Ferré, 2014 ; Ishi et al, 2014 ; Ambrazaitis and House, 2017 ; Esteve-Gibert et al, 2017a ), and it also seems to hold for infants and children ( Butcher and Goldin-Meadow, 2000 ; Esteve-Gibert and Prieto, 2014 ; Mathew et al, 2017 ). While more research is needed to examine the patterns of this temporal linkage in infants’ productions (especially in stages when these prosodic targets become adult-like), perception studies show that infants are sensitive to the alignment of prosodic and visual cues as early as 8–9 months of age ( Kitamura et al, 2014 ; Esteve-Gibert et al, 2015 ). It has been proposed that the driving force of this temporal linkage is a bi-directional influence between gesture and speech ‘pulses’ (i.e., peaks in an ongoing rhythm) ( McNeill, 1992 ; Tuite, 1993 ; Iverson and Thelen, 1999 ; Port, 2003 ; Rusiewicz and Esteve-Gibert, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…They found that infants aged 10–11 months use visual prosody to extract information about the structure of language as they matched synchronous faces and voices. More recently, it has been shown that 8-month-old infants reliably detect congruence between matching auditory and visual displays of a talking face based on prosodic motion ( Kitamura et al, 2014 ), and that 9-month-olds can detect whether a manual deictic gesture is congruently aligned with the corresponding speech segment ( Esteve-Gibert et al, 2015 ). Using an intermodal matching paradigm, Kitamura et al (2014) presented 8-months-old infants with two visual displays of talking faces (i.e., only moving dots) and one utterance that matched one of the two facial configurations.…”
Section: Implications Of the Audio–visual Integration For Word Learnimentioning
confidence: 99%
“…En esta línea, se sitúan diferentes trabajos que han analizado la coordinación simultánea con el habla de gestos deícticos con una función declarativa o imperativa, proporcionando evidencias que permiten afirmar que el gesto y el habla forman un sistema integrado en el acto comunicativo, tal y como sucede entre los adultos (Esteve-Gibert, Prieto & Pons, 2015). En otras palabras, los bebés pueden utilizar intencionalmente estrategias multimodales para marcar una prominencia en sus producciones comunicativas, comportamiento que favorece los procesos de atención conjunta, y refuerza la acción triádica entre el niño, un adulto y un objeto.…”
Section: Fundamentación Teóricaunclassified